Visualizing the Research Hotspots and Emerging Trends in Neural Tube Defects: A Review - Baohong MAO; Chichen ZHANG; Liping YANG; Yanxia WANG; Chunhui SU; Huining ZHAO; Yawen SHAO; Qing LIU (Tehran University of Medical Sciences, 2020)
Background: Neural tube defects (NTDs) are among the second most common serious birth defects and constitute a major cause of infant death. Research about NTDs has achieved tremendous progress over the last 50 years. Methods: Visualization analysis has been used to explore the hot topic and their emerging trends in NTDs research domain. The scientiﬁc literature of research for NTDs has been retrieved from Web of Science™ Core Collection (1966-2014) databases, and final acquire 9125 related bibliographic records, then analyze time trend, distribution of journals, hot keywords, and try to explore the hot topic and their emerging trends in NTDs research domain using Histcite and CiteSpace. Results: The number of publications about NTDs have shown an increased tendency over the last 50 years although there was on a slight decline. Birth Defects Research Part A published the most articles on NTDs research, followed by Lance and Teratology, and the Lancet had the greatest number of total citations. The largest cited frequency keywords was the "Folate", followed by "Pregnancy", "Prevention", and "Spina bifida". The research hotspots in NTDs research were homocysteine, anencephaly, and screening. Conclusion: With the help of visualization analysis, we explore a quantitative and efficient way of understanding the NTDs knowledge field.